2004
DOI: 10.1098/rspb.2003.2523
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecology of Triassic stem turtles sheds new light on turtle origins

Abstract: Competing hypotheses of early turtle evolution contrast sharply in implying very different ecological settings-aquatic versus terrestrial-for the origin of turtles. We investigate the palaeoecology of extinct turtles by first demonstrating that the forelimbs of extant turtles faithfully reflect habitat preferences, with short-handed turtles being terrestrial and long-handed turtles being aquatic. We apply this metric to the two successive outgroups to all living turtles with forelimbs preserved, Proganochelys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
199
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(207 citation statements)
references
References 35 publications
8
199
0
Order By: Relevance
“…Eileanchelys waldmani Anquetin, Barrett, Jones, Moore-Fay and Evans, 2009 and Herckerochelys romani Sukhanov, 2006: Scheyer et al 2014; also Condorchelys antigua Sterli, 2008: Cerda et al 2015, the majority of stem turtles showed terrestrial habitat preference (e.g. Joyce and Gauthier 2004;Sterli et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eileanchelys waldmani Anquetin, Barrett, Jones, Moore-Fay and Evans, 2009 and Herckerochelys romani Sukhanov, 2006: Scheyer et al 2014; also Condorchelys antigua Sterli, 2008: Cerda et al 2015, the majority of stem turtles showed terrestrial habitat preference (e.g. Joyce and Gauthier 2004;Sterli et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Joyce et al (2011), on the other hand, argued for terrestrial habits of solemydid turtles based on anatomical data, such as the presence of limb ossicles. Unfortunately, the described solemydid turtles so far did not include articulated forelimbs, which could otherwise be used to elucidate their palaeoecology, as has been done previously for Triassic stem turtles Proganochelys quenstedti Baur, 1887 and Palaeochersis talampayensis Rougier, de la Fuente and Arcucci, 1995 (Joyce and Gauthier 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Complete limbs are mostly known for "eurysternids" and "plesiochelyids." In general, these are characterized by a moderately elongated stylopod, a shorter zeugopod, and a relatively elongated autopod similar in proportion to extant pleurodires and trionychids (Joyce and Gauthier 2004). Well-developed articular surfaces reveal that thalassochelydians did not possess stiffened paddle as in extant marine turtles, but the flippers of Neusticemys neuquina were described as having been less mobile than those of trionychids (de la Fuente and FernĂĄndez 2011).…”
Section: Shellmentioning
confidence: 99%
“…Closed middle ear cavities are not seen until the Eocene [11]. On the other hand, front limb proportions, shell shape and histology suggest that other near-crown stem turtles were terrestrial [46,47]. In addition, Eunotosaurus and successive out-groups lack obvious aquatic adaptations and are only known from terrestrial sediments [48].…”
Section: Discussionmentioning
confidence: 99%